Analysis of Factors Influencing Chili Production Using the Spatial Regression Method - Ananda, Laraswati; Gusnayanti, Riski; Ratmaji, Muji; Soraya, Siti; Firmansyah, Firmansyah (Journal of Mathematics and Applied Statistics, 2025)
Chili pepper production in West Nusa Tenggara is the second largest producer in Indonesia. However, the distribution of production still shows a significant imbalance between regions. This imbalance can affect the stability of supply and prices both locally and nationally. This study aims to examine the factors that influence chili pepper production in NTB using the spatial regression method. The data used are secondary data from agricultural statistics in 2024, which cover ten districts/cities. The SEM model was chosen because it can identify the effects that occur between geographically close regions, which are often not visible in traditional regression models. The results of the analysis show that the area of ​​harvested land and the level of chili pepper productivity have a significant effect on the total production at a real level of 10%, with coefficients of 96.6132 and 44,385.5, respectively. The lambda value reaching 1.6667 provides support for evidence of positive spatial autocorrelation between regions. The SEM model also showed a lower AIC value (316.58) compared to the classical regression model, indicating that this model is more efficient and accurate.